Thin-plate spline analysis of mandibular shape changes induced by functional appliances in Class II malocclusion A long-term evaluation - Franchi, Lorenzo; Pavoni, Chiara; Faltin, Kurt; Bigliazzi, Renato [UNESP]; Gazzani, Francesca; Cozza, Paola (Urban & Vogel, 2016)
Aims The purpose of this work was to evaluate the longterm morphological mandibular changes induced by functional treatment of Class II malocclusion with mandibular retrusion. Methods Forty patients (20 females, 20 males) with Class II malocclusion consecutively treated with either a Bionator or an Activator followed by fixed appliances were compared with a control group of 40 subjects (19 females, 21 males) with untreated Class II malocclusion. Lateral cephalograms were available at the start of treatment (T1, mean age 9.9 years), at the end of treatment with functional appliances (T2, mean age 12.2 years), and for long-term follow-up (T3, mean age 18.3 years). Mandibular shape changes were analyzed on lateral cephalograms of the subjects in both groups via thin-plate spline (TPS) analysis. Shape differences were statistically analyzed by conducting permutation tests on Goodall F statistics. Results In the long term, both the treated and control groups exhibited significant longitudinal mandibular shape changes characterized by upward and forward dislocation of point Co associated with a vertical extension in the gonial region and backward dislocation of point B. Conclusion Functional appliances induced mandible's significant posterior morphogenetic rotation over the short term. The treated and control groups demonstrated similar mandibular shape over the long term.
Keywords: Class II malocclusion; Functional appliances; Thin-plate spline analysis; Cephalograms